The cis-Regulatory Element of SNCA Intron 4 Modulates Susceptibility to Parkinson’s Disease in Han Chinese - Zhu, Shi-Guo; Lu, Hui; Mao, Miao; Li, Zhao-Feng; Cui, Lei; Ovlyakulov, Begench; Zhang, Xiong; Zhu, Jian-Hong (Frontiers in Genetics, 2020)
Objective: A novel functional cis-regulatory element (CRE) located at SNCA intron 4 has recently been identified in association with Parkinson’s disease (PD) risk in European descendants. We aimed to investigate whether this CRE is associated with PD in Han Chinese ethnicity. Methods: A Chinese cohort comprising 513 sporadic PD patients and 517 controls was recruited. CRE variants were identified by sequencing and then analyzed. Results: A total of 9 variants were detected, including eight single nucleotide variants and one new insertion variant. Two variants, rs17016188 and rs7684892, had minor allele frequency greater than 5%. A difference of rs17016188 was observed in the males with the C allele serving as a recessive risk factor (P = 0.001, OR = 2.349, 95% CI = 1.414-3.901) following Bonferroni correction. Haplotypes of rs17016188 and rs7684892 showed distribution differences in the total and the male populations (P = 0.002 and 4.0810-5, respectively). Amongst, rs17016188/T-rs7684892/G was associated with a reduced risk for PD (P = 4.8  10-4, OR = 0.731, 95% CI = 0.614-0.872). Conclusions: Our results provide insight into how the SNCA intron 4 CRE harbors variants and its contribution to PD risk in Chinese ethnicity.